2007
DOI: 10.7824/rbh.v6i2.57
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação do controle químico de plantas daninhas através de diferentes formas de absorção

Abstract: Resumo-O trabalho objetivou quantificar a intensidade de ação de herbicidas no controle de Brachiaria decumbens (BRADC) e Digitaria horizontalis (DIGHO), através de diferentes formas de absorção. Para tanto, três experimentos foram conduzidos em estufas plásticas representados pelos herbicidas atrazine (3,00 kg i.a. ha-1 + óleo mineral Assist ® 0,5% v/v), oxyfluorfen (0,72 kg i.a. ha-1) e isoxaflutole (0,06 kg i.a. ha-1), aplicados em pós-emergência inicial. Três possibilidades de absorção (radicular, foliar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…For foliar absorption pathway, it was observed that only mesotrione + atrazine association presented satisfactory control at 14 DAA, being this effect significantly lower to root absorption pathway and foliar + root absorption pathway, but characterized as synergistic action. Maciel et al (2007) also observed that isolated atrazine application did not promote satisfactory control of D. horizontalis in any of pathways absorption studied. Table 4.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…For foliar absorption pathway, it was observed that only mesotrione + atrazine association presented satisfactory control at 14 DAA, being this effect significantly lower to root absorption pathway and foliar + root absorption pathway, but characterized as synergistic action. Maciel et al (2007) also observed that isolated atrazine application did not promote satisfactory control of D. horizontalis in any of pathways absorption studied. Table 4.…”
Section: Resultsmentioning
confidence: 82%
“…For treatments with soil isolation, it was used aluminum foil secured with duct tape to protect the entire soil surface of experimental units, exposing only plants aerial part to spray nozzles, according to methodology described by Maciel et al (2002;2007). Thirty minutes after herbicides applications in post-emergence, plastic straws and aluminum foil were carefully removed, avoiding plants contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture of oxyfluorfen and flumioxazin with the addition of mineral oil provided low efficiency in controlling Digitaria horizontalis (Jamaican crabgrass); this is confirmed by the high importance value index (IVI) of this species, reaching 100% or more at all the mixture doses (Figure 1). The low efficiency in controlling D. horizontalis by the herbicide oxyfluorfen was confirmed by Maciel et al (2007), where control reached a maximum of 23% in different soil types and modes of absorption. Carvalho et al (2014) also did not reach an effective control for the genus Digitaria with the application of oxyfluorfen on the irrigated onion culture.…”
Section: Resultsmentioning
confidence: 87%